2021
DOI: 10.1111/all.14907
|View full text |Cite
|
Sign up to set email alerts
|

Caspases and therapeutic potential of caspase inhibitors in moderate–severe SARS‐CoV‐2 infection and long COVID

Abstract: Background: COVID-19 can present with lymphopenia and extraordinary complex multiorgan pathologies that can trigger long-term sequela.Aims: Given that inflammasome products, like caspase-1, play a role in the pathophysiology of a number of co-morbid conditions, we investigated caspases across the spectrum of COVID-19 disease. Materials & Methods:We assessed transcriptional states of multiple caspases and using flow cytometry, the expression of active caspase-1 in blood cells from COVID-19 patients in acute and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 86 publications
(143 reference statements)
3
50
0
Order By: Relevance
“…Among the top Δβ-value methylation changes comparing pre- and post-COVID-19 timepoints, we observed two differentially methylated loci (cg02037503 and cg23712970) in a gene promoter transcription start site regulatory region of the apoptotic chromatin condensation inducer 1 ( ACIN1 ) gene Supplementary Figure S2 that decreased in DNA methylation following COVID-19 by approximately 15% for both CpG sites ( Fig.1d,e ). This gene codes a nuclear protein that induces apoptotic chromatin condensation after activation by caspase-3 (Sahara et al, 1999), which we previously reported was increased in red blood cells of hospitalized COVID-19 participants (Plassmeyer et al, 2021). We also observed differential methylation at cg10846936 related to the caspase recruitment domain family member 14 ( CARD14 ) gene that is involved in activating nuclear factor-kappa-B involved in immune inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Among the top Δβ-value methylation changes comparing pre- and post-COVID-19 timepoints, we observed two differentially methylated loci (cg02037503 and cg23712970) in a gene promoter transcription start site regulatory region of the apoptotic chromatin condensation inducer 1 ( ACIN1 ) gene Supplementary Figure S2 that decreased in DNA methylation following COVID-19 by approximately 15% for both CpG sites ( Fig.1d,e ). This gene codes a nuclear protein that induces apoptotic chromatin condensation after activation by caspase-3 (Sahara et al, 1999), which we previously reported was increased in red blood cells of hospitalized COVID-19 participants (Plassmeyer et al, 2021). We also observed differential methylation at cg10846936 related to the caspase recruitment domain family member 14 ( CARD14 ) gene that is involved in activating nuclear factor-kappa-B involved in immune inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…These observations point out to an immunological basis in the different course of the disease according to gender [37], and it could be theorized that these characteristics -the strong CD8 T-cell response, as well as the activation of TLRs and the inflammasome [39]-, are likely involved in the differences by sex observed in PCS.…”
Section: Pcs and Gendermentioning
confidence: 97%
“…Endothelial dysfunction, small vessel microangiopathy, fibrin clotting within small capillaries may also contribute to decreased effective oxygen carrying capacity and contribute to shortness of breath and exercise intolerance 64 . A hyperinflammatory syndrome with persistent immune activation and dysregulation of the immune response has also been suggested as a possible mechanism for some of the symptoms 65 , 66 . The histopathological detection of autoreactive T cells in autopsy samples from individuals infected with COVID-19 supports this latter mechansim 67 , 68 .…”
Section: Pathophysiologymentioning
confidence: 99%